Recent Progress in the Chemistry of 2-Unsubstituted 1H-Imidazole 3-Oxides - Mloston, Grzegorz; Jasinski, Marcin; Wróblewska, Aneta; Heimgartner, Heinz (Current Organic Chemistry, 2016)
The 2-unsubstituted 1H-imidazole 3-oxides, considered as ‘nitrone-like’ azaheterocycles, are well known as versatile building blocks, useful for the preparation of more complex systems containing an imidazole moiety. Their applications in diverse reactions, such as isomerization to corresponding imidazol-2-ones, [3+2]-cycloadditions, sulfur transfer reactions leading to imidazole-2-thiones, heterocyclizations leading to fused heterocyclic systems, as well as cross coupling reactions are discussed. New methods for the preparation of enantiomerically pure 1Himidazole 3-oxides and their applications in asymmetric reactions, synthesis of room temperature ionic liquids and biologically active compounds are also reviewed.
Keywords: [3+2]-cycloaddition